Growth of Ag-Nanoparticles: Shape-Directing Role of Silver Ions and Stabilizer in Aqueous Solutions - Zaheer, Zoya; Rafiuddin, Rafiuddin (JOURNAL OF ADVANCES IN CHEMISTRY, 2010)
Silver nanoparticles were synthesized using Tulsi leaves extract as reducing as well as a capping agent to reduce the steps and parameters involved in the synthesis. The morphology, stability and optical properties of Ag-nanoparticles depend on reactants and stabilizer, cetyltrimethylammonium bromide (CTAB) concentrations. The silver nanoparticles were characterized by UV-visible spectrophotometer, and transmission electron microscope (TEM). Spherical morphology of the silver nanoparticles with an average diameter ofÂ 25 nm. Morphology changed markedly from spherical aggregated to highly polydispersed in presence of CTAB.